Multidimensional entrepreneurship: theoretical considerations and Swedish empirics - Hans Westlund (European Regional Science Association (ERSA), 2010)
Entrepreneurship is often viewed in a simplified way and defined as the starting of new firms. There are obvious advantages in using this simplified definition, not least regarding measurement, but with such a definition there is also a great risk in missing important aspects of entrepreneurship and how it emerges and develops. This paper starts from an assumption that entrepreneurship can be divided in four different spheres and that these spheres interact and mutually affect each other. The four spheres of entrepreneurship are: - Economic entrepreneurship, which is manifesting itself in new enterprises and products, production, distribution and sales methods and organizations. - Civil entrepreneurship, in the form of new organizations and new activities in the civil society and human relations. - Political entrepreneurship, e.g. in the form of new types of policies, governance, decision-making and implementation processes. - Academic entrepreneurship, displayed in innovative research (new hypotheses, methods, applications, etc), collaboration with other actors and commercialization of results. It can be assumed that the four forms of entrepreneurship mutually are having impacts on each other, but that the directions of these impacts can vary. On the one hand it is possible that the four types of entrepreneurship show a mutually positive relationship, on the other hand it is just as possible that the different entrepreneurships might exclude each other as they compete for the engagement of a finite number of entrepreneurs in a region. This paper makes a first investigation of the four dimensions of entrepreneurship in Sweden and the connections between them and various measures of growth on municipality level.
Keywords: 330